Legal Standing Provision to The Community on Disputes Over The Results of Regional Elections With A Single Candidate In Constitutional Court - Yakub, Sandra Leoni Prakasa Yakub; Ayuni, Qurrata (LPPM Universitas Lampung, 2022)
This article discusses Constututional Court Regulations Number 6 of 2020 which regulates parties who can be applicants in disputes over the results of Regional election with a single candidate are only candidate itself and election monitors, but ignores the right for community to become applicants. This paper argues that legal standing in disputes over the results of regional head elections with a single candidates should also be given to the community based on: community is a real subject involved in elections, and has an impact on the election of regional heads, the right to argue and actualize themselves in the democratic process, then the state should be able to open an opportunity for the public. The approach method used is normative juridical with secondary data. This paper concludes with the existence of a mechanism that provides access to the public as applicants in disputes over the results of regional elections with one pair of candidates, the community does not only play a role in choosing the options offered by the political system but is able to speak out over the circumstances created by the system.